Tamil Nadu survey manual for modern survey using global positioning systems (GPS) and electronic total stations (ETS) - Kannan, R (Chennai, 2012)
The present volume, Volume-IV has been written due to the revolution in the methods of survey and maintenance of land records due to the introduction of electronic instruments for survey and Information Technology (L.T.). This volume deals with how to use the (LT.) in surveying.
Keywords: Tamil Nadu Syrvey Manual